Flow patterns of non-Newtonian nanofluid flow in cylindrical enclosure with rotating endwall: Effects of nanoparticles concentration - Ragueb Haroun (EDP Sciences, 2021)
In this paper, a numerical study on the flow structure of non-Newtonian nanofluid in cylindrical enclosure with rotating end wall. The considered nanofluid, MWCNT-water, exhibits a strong power-law shear-thinning behavior with the increase in nanoparticles loading. The main focus in this study is the effect of nanoparticles concentration on the vortex breakdown phenomenon. The simulation results showed that adding a small amount of nanoparticle eliminate the vortex breakdown which is considered as a positive in mixing process. However, the increase in nanoparticles concentration as well as the enclosure aspect ratio promotes the apparition of secondary recirculation zone and stagnation zone.